Students' Perceptions of Memrise App Use in Learning Vocabulary - Baniara, Mirdad; Halim, Abdul; Abidin, Azwar (AL LUGHAWIYAAT, 2023)
This study aims to investigate the students’ perceptions in using Memrise app in learning vocabulary. To achieve this aim, this research applied qualitative methodology as qualitative research. The participants of this study were 20 students with non-English major study programs. The data of this study were obtained from students’ written reflections through Google form that spread by WA Group. Thematic analysis was implemented in this study based on the concept of students’ perceptions. The result of the analysis showed that students’ perceived usefulness in learning vocabulary with the Memrise application has positively increased. The students also felt entertained in learning vocabulary, such as playing a game. The result also revealed that students implemented their words knowledge in speaking, pronunciation, listening and writing. The students were satisfied in learning vocabulary after exposing them with range of built-in features of the application, such as videos, audios, pronunciation guidance and reviewing learning systems. The pedagogical implication of this study is that the teacher/lecturer, university, and students can utilize this application as learning and teaching media to bridge them to acquire good range of lexical.Keywords: Learning Vocabulary; MALL; Memrise App; Students’ Perceptions